DIGITAL MARKETING STRATEGY IN INCREASING BRAND AWARENESS OF TECHNOLOGY STARTUPS - Nova Yanti Maleha (Adisam Publisher, 2024)
Digital Marketing is one of the marketing media that is currently in great demand by the public to support various activities carried out. Increasing sales competition is increasingly fierce, encouraging companies to place greater emphasis on adequate digital marketing strategies as a way of introducing products to the public, this term is called brand awareness. With increasingly sophisticated technological advances, businesses also have to adapt as quickly as possible. Brand awareness must also be increased in creative ways and not just like that. Brand awareness is very important in every business. Consumers' decisions to buy a product will be greatly influenced by the level of brand awareness of the product. Pull Strategy provides unique features in the application to make customers satisfied and happy in their work, as well as using Instagram social media to promote products/services, what events and giveaways will be held, promos, providing general knowledge packaged creatively, and publication through broadcast media, namely radio. Engagement with customers/consumers can increase awareness of the brand. Thus, the importance of social media as a tool that can help increase personal connections is by starting to gain participation from businesses and consumers.